Speed controlling of the PEM fuel cell powered BLDC motor with FOPI optimized by MSA - Yigit, Tevfik; Celik, Hakan (Pergamon-Elsevier Science Ltd, 2020)
In this study, Brushless DC (BLDC) motor, which is commonly used as a drive element in the unmanned aerial vehicle (UAV), electric vehicles, and mobile robots today, is powered by hydrogen technologies as environmentally friendly and controlled by a fractional-order PI (FOPI) controller structure. Proton Exchange Membrane (PEM) electrolyzer, PEM Fuel Cell (PEMFC), storage tank, BLDC motor, and motor driver system are modeled and integrated into the Simulink environment in MATLAB. PEM electrolyzer that is energized from the AC grid via the AC/DC converter generates the hydrogen. This generated hydrogen is stored in the storage tank and used by PEMFC to energize to the BLDC motor. The model of the BLDC motor is controlled by using a closed-loop FOPI controller for the variable speed and torque reference values. Parameters of the FOPI are determined by Moth Swarm Algorithm (MSA) optimization method. It is observed from the results that the PEMFC powered FOPI controlled BLDC motor operates stably at high performance for different speed and torque values as expected from the modern drive systems. Furthermore, it is seen that the required energy for the BLDC motor is provided by the PEMFC-PEM electrolyzer system without interruption and the FOPI controlled BLDC motor successfully follows the reference speed values for the different torque values. (c) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: PEM electrolyzer; PEM Fuel cell; BLDC motor; Simulink model; Dynamic model; System simulation